Dietary supplement usage and their association with sociodemographic factors among gym male participants in selected areas of the Jaffna district - Ananthakrishnan, G.; Rajeevan, S.; Thabotharan, D.; Ahilan, B. (University of Jaffna, 2024)
Introduction: The prevalence of dietary supplement usage for fitness objectives is rising, particularly among gym participants, and is influenced by diverse sociodemographic factors. Recognizing these connections is important for planning interventions to enhance health outcomes and facilitate informed decision-making within this demographic. Objective: To assess dietary supplement usage and the association with socio- demographic factors on supplement utilization among male gym participants in the Jaffna district. Methodology: A descriptive cross-sectional study was conducted among gym attendees in Jaffna, including Nallur, Kopay, Chavakachcheri, and Point Pedro. Male participants aged 18 to 60 years were randomly selected. Data was collected via interviewer-administered questionnaires. Statistical analysis was performed using SPSS 20 software, and ethical clearance was obtained from the Ethical Review Committee, Faculty of Medicine, University of Jaffna. Results: The study comprised 422 participants with a 100% response rate. A majority (50.7%) were classified as overweight, and 62.8% were aged over 35 years. Most participants did not utilize supplements; among those who used supplements with the primary focus on bodybuilding. Dietary supplement usage exhibited significant associations with age (p<0.001), BMI (p<0.001), and education level (p<0.001). Conclusion: Gym attendees use various supplements, predominantly for general fitness purposes. Sociodemographic factors such as age, BMI, and education level significantly influence supplement usage patterns among participants.
Keywords: Knowledge; Attitude; Practice; Dietary Supplements; Divisional Secretaries; Gym Participants